Analisis Harga, Kualitas Produk dan Saluran Distribusi (Studi Kasus Pada Konsumen Tenun Ikat “Xyz” Jepara) - Alifatur Rohmah; Setiyono Setiyono; Ratna Listiyana Dewi (EBBANK, 2019)
This study aims to analyze to price, product quality and distribution channel. The study was conducted at tenun ikat “Xyz” Jepara, respondents in this study were customer who purchased products at least once, respondents in this study were customer who purchased products at least once, respondents tenun ikat “Xyz” Jepara as many 56 people. Based on the results of the study show that the product quality and distribution channel get good criteria, while the price variable are still not good. On the product quality the highest value is obtained from aesthic dimension, the lowest value obtained from the dimension of additional privileges, value distribution caverage. The price variabel are still not good. On the product quality the highest value is obtained from aesthetic dimension, the lowest value obtained from the dimensions of additional privilages, value distribution channel the highest channel type dimensions, the lowest value obtained from distribution coverage. Variable is the highest value on the price compability with product quality the lowest value obtained from price comformity with benefits dimension.